Towards an explanation of cross-country asymmetries in monetary transmission - Georgios Georgiadis (Deutsche Bundesbank, 2012)
I quantify the importance of financial structure, labor market rigidities and industry mix for cross-country asymmetries in monetary transmission. To do so, I determine how closely the impulse responses to a monetary policy shock obtained from country-specific vectorautoregressive (VAR) models and a non-standard panel VAR model match. In the country-specific VAR models, the impulse responses vary across countries in an unrestricted fashion. In the panel VAR model, the impulse responses also vary across countries, but only to the extent that countries differ regarding their financial structure, labor market rigidities and industry mix. For a sample of 20 industrialized countries over the time period from 1995 to 2009, I find that up to 70% (50%) of the cross-country asymmetries in the responses of output (prices) to a monetary policy shock can be accounted for by crosscountry differences in financial structure, labor market rigidities and industry mix. While in the short run asymmetries in the output responses arise mainly due to cross-country differences in industry mix, in the medium and long run differences in financial structure and labor market rigidities gain more importance. Moreover, cross-country differences in industry mix appear to be of rather minor importance for cross-country asymmetries in the transmission of monetary policy to prices.
Keywords: C33; C51; E44; E52; 330; Monetary Transmission; Financial Structure; Labor Market Rigidities; Industry Mix; Panel VAR; Heterogeneity; Transmissionsmechanismus; Geldpolitik; Schock; Kapitalstruktur; Arbeitsmarktflexibilität; Wirtschaftsstruktur; Schätzung; Vergleich; Industriestaaten